Multidrug resistant (MDR) and extensively drug-resistant (XDR) gram negative bacteria at a tertiary care hospital, in Lalitpur, Nepal - Rajbhandari, Piyush; Maharjan, Shanta; Aryal, Sushant; Pradhan, Prasil; Prajapati, Silvie (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Prevalence of multi and extensively drug resistant (MDR and XDR) gram negative bacteria (GNB) are increasing trend and becoming a threat to public health. There is no single effective antibiotic to treat these pathogens. These superbugs need continuous surveillance to develop relevant treatment protocols and early therapeutic approaches. In this study, we evaluated the trends in prevalence, etiology and antibiogram of MDR and XDR GNB isolated from various samples in a tertiary care hospital.Method: It was a hospital based descriptive cross-sectional study conducted at Patan Hospital, Patan Academy of Health Sciences. All the records of the patient whose culture and sensitivity report yielded gram negative bacteria from 1st January 2021 to 31st December of 2023 was extracted from the hospital electronic database and analyzed. Ethical approval was taken from the institutional review committee.Result: The prevalence of MDR GNB was found to be at 22.30%. The prevalence of XDR GNB among the total isolated GNB was 9.41%. Acinetobacter baumanii complex, Klebsiella spp., Escherichia coli and Pseudomonas aeruginosa were the most common MDR and XDR pathogens encountered. For the antibiotics tested, a higher number of isolates were susceptible to carbapenem group (32%) followed by aminoglycosides (28.3%) doxycycline (26%) and piperacillin-tazobactam (17.4%).Conclusion: More than 22% of patients with GNB infection were multidrug resistant. Aminoglycosides and carbapenems are good options for treatment of MDR-GNB infection however treatment should be based on culture and sensitivity reports. When treating XDR-GNB infection, adding doxycycline can also be considered.